Effects of minocycline on epiplexus macrophage activation, choroid plexus injury and hydrocephalus development in spontaneous hypertensive rats. Issue 10 (October 2019) - Gu, Chi; Hao, Xiaodi; Li, Jianru; Hua, Ya; Keep, Richard F; Xi, Guohua
Hydrocephalus has been reported to occur in spontaneous hypertensive rats (SHRs). The purposes of this study were (1) to use T2 magnetic resonance imaging to examine time of onset, (2) to elucidate potential underlying mechanisms and (3) to determine whether minocycline could prevent hydrocephalus development. Ventriculomegaly was evaluated by T2 imaging in SHRs and Wistar-Kyoto rats from weeks 4 to 7 after birth. Brain histology and transmission electron microscopy were used to assess the periventricular and choroid plexus damage. SHRs were also treated with either vehicle or minocycline. We found that hydrocephalus was observed in SHRs but not in Wistar-Kyoto rats. It occurred at seven weeks of age but was not present at four and five weeks. The hydrocephalus was associated with epiplexus cell (macrophage) activation, choroid plexus cell death and damage to the ventricle wall. Treatment with minocycline from week 5 attenuated hydrocephalus development and pathological changes in choroid plexus and ventricular wall at week 7. The current study found that spontaneous hydrocephalus arises at ∼7 weeks in male SHRs. The early development of hydrocephalus (persistent ventricular dilatation) may result from epiplexus cell activation, choroid plexus cell death and periventricular damage, which can be ameliorated by treatment with minocycline.